Desconcentração da polícia técnica e científica do Estado de Rondônia: uma política de administração pública - Gouvêa, Gutemberg de Araujo (2012)
The present study aims to expound the deconcentration of the Scientific and Technical Division of the Police Department in the brazilian state of Rondônia, to collaborate for local organs management and also to assist in the social control by the citizen, with the origination of regional level coordination offices within this Police Department division. Using the Rondônia's Forensic Experts Forum, through the Internet, it was released selected questions about the concepts of once discussed themes and also about the perspectives of changes in the form of criminal forensics in the Rondônia state provinces. In addition, it has been accomplished data analysis of population, geographic locations, police reports and number of criminal forensics officers; bibliographic reviews and documental searches. The poll applied with criminal forensics professionals reveals unfamiliarity related to the difference between the key concepts shown in this study, although they reconizes the need of a deconcentration in the Scientific and Technical Division of this Police Department. This deconcentration purposes mostly the recognition of the regional sectors and the improvement of the work provided to society. The data related to the field of each sector inside Institute of Criminalistics, including current and dismantled ones, were analyzed. After that, the need of deconcentration of the criminal forensics in the inner state of Rondônia became even clearer, which proves the urgent need about origination of management sectors attuned to the central organ, yet only if performed as public politics.